Child health and survival in urban slums in Malawi : healthcare seeking practices and relative significance of health system factors in influencing care seeking decisions among care givers of under-five children - Lungu, Edgar Arnold (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2014)
Despite significant improvements in child health indicators over the past few decades globally and in Malawi, various challenges remain. Globally, cost effective interventions to promote child health exist but coverage for some of them remains low, thereby affecting optimal attainment of child health and survival benefits from these interventions. In addition, the increasing urbanisation and urbanisation of poverty in sub- Sahara Africa including Malawi is manifesting in an increasing population living under slum conditions which pose significant health challenges for vulnerable population groups such as under-five children.
Keywords: Health Systems, Ph.D.; Ph.D. Trinity College Dublin